Pre-Competition Preparation Stages Of 16-17- Year-Old Greco-Roman Wrestlers - Abdullayev Ilham Khushnudovich (Zien Journals, 2024)
In this investigation a proposal is made for the organization of the tactical preparation in Greco-Roman wrestling for youth. It has three phases; diagnosis, organization and evaluation of the process. Also, this article describes how to prepare before participating in Greco-Roman wrestling and what are the stages at each age limit.
Keywords: Greco-Roman wrestling; sport; development; experimental group